1992
DOI: 10.1007/bf00225992
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic trend of persistent organochlorine contamination in wildlife from a tropical agricultural watershed, South India

Abstract: The residue levels of persistent organochlorines, such as HCH (BHC: 1,2,3,4,5,6-hexachlorocyclohexane) isomers, DDT [1,1,1-trichloro-2,2-bis (p-chlorophenyl) ethane] compounds, PCBs (polychlorobiphenyls) and HCB (hexachlorobenzene), were measured in wildlife. The wildlife were sampled from terrestrial and aquatic habitats in and around the agricultural watershed of Parangipettai, South India. On the basis of overall concentrations sigma HCH ranked first followed by sigma DDT, sigma PCB and HCB, reflecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
4
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 23 publications
4
28
4
1
Order By: Relevance
“…These values were similar to the corresponding data determined in loaches (Table 1). Compared with published data, the total concentrations of HCH in mitten-handed crabs from this study was less than those in the river crab (643 ng g −1 lw) from Qiantang River of China [26], and also much less than those in mangrove crab (62 ng g −1 ww) from South India [19]. However, the mitten-handed crabs has the higher contents of HCB compared with mangrove crab from South India [19].…”
Section: Bioaccumulation Of Organochlorine Pesticidescontrasting
confidence: 83%
See 3 more Smart Citations
“…These values were similar to the corresponding data determined in loaches (Table 1). Compared with published data, the total concentrations of HCH in mitten-handed crabs from this study was less than those in the river crab (643 ng g −1 lw) from Qiantang River of China [26], and also much less than those in mangrove crab (62 ng g −1 ww) from South India [19]. However, the mitten-handed crabs has the higher contents of HCB compared with mangrove crab from South India [19].…”
Section: Bioaccumulation Of Organochlorine Pesticidescontrasting
confidence: 83%
“…Therefore, the ratio of (DDD+DDE)/∑DDT is a good indicator of DDT biodegradation [19]. In this study, mitten-handed crabs had the highest average ratio of (DDD+DDE)/∑DDT of 0.97, followed by loaches (0.91) ( Figure 5).…”
Section: Bioaccumulation Of Organochlorine Pesticidesmentioning
confidence: 64%
See 2 more Smart Citations
“…Significantly higher concentration of PCBs and DDTs were found in Chinese-pond heron due to its piscivorous habitat (Chang et al 2003). Previous studies have revealed that the level of organochlorine compound in piscivorous bird was higher than that in insectivore and herbivores ones (Ramesh et al 1992;Naso et al 2003). The order for the level of PCBs and DDTs among species was as follows: Chinesepond heron > white-breasted waterhen ≥ common snipe > slaty-breasted rail ≥ ruddy-breasted crake.…”
Section: Interspecies Difference and Influence Of Trophic Level (δ 15mentioning
confidence: 93%